HUBUNGAN ANTARA KECERDASAN SPIRITUAL DENGAN PERILAKU PROSOSIAL PADA MAHASISWA - Rizki Deco Saputra Harahap, Ernanda; Argasiam, Brigitan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2025)
This study aims to determine the relationship between spiritual intelligence with prosocial behaviour in psychology students at Soegijapranata Catholic University in Semarang. The hypothesis proposed is a positive relationship between spiritual intelligence and prosocial behaviour in students. The subjects were students of the Psychology Faculty at the Soegijapranata Catholic University Semarang. This research is an Accidental Sampling Technique. Respondents taken were a number of 50 respondents. The scale in this study is the scale of spiritual intelligence and prosocial behaviour. The data analysis method used is Product Moment Correlation. The results of the data show rxy = 0.386 with p = 0.003 (p<0.05). the results show that there is a positive relationship between spiritual intelligence and prosocial behaviour in students, which means that the higher the spiritual intelligence, the higher the prosocial behaviour in students, and vice versa. Based on the results of the analysis of the prosocial behaviour in students and vice versa. Basen on the results of the analysis of the hypothesis test it can be concluded that the hypothesis is accepted. Keywords: Spiritual Intelligence, Prosocial Behavior, Students.